PENGARUH DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DI PT BRIDGESTONE PONDOK BANDAR JAMBU KABUPATEN SIMALUNGUN - Hengki Mangiring Parulian Simarmata; Doris Yolanda Saragih; Nora Januarti Panjaitan (Politeknik Bisnis Indonesia, 2021)
Work discipline can improve company progress. This study aims to determine the influence of employee work discipline on employee performance at PT Bridgestone Pondok Bandar Jambu, Simalungun Regency. This research is a quantitative study using all employees as the sample. Data collection techniques is done by distributing questionnaires, observation, and documentation. The results of the data were obtained by using SPSS, the data were tested by validity test, reliability test, Kolmogorov-Smirnov test, normality test, and simple linear analysis. From the research results, there is a significant positive effect of work discipline on employee performance where the magnitude of the influence of the discipline variable is 51.6% while the remaining 48.4 % is influenced by other variables that are not examined in this study such as work environment variables, leadership style, and others.